Hubungan Guru dan Murid dalam Pendidikan Agama Islam Menurut Kajian Q.S. Al-Kahfi Ayat 65-70 - Pratama, Ervan Saleh (Tadabbur: Jurnal Peradaban Islam, 2020)
The research is based on the writer's interest in knowing how exactly the relationship between a teacher and student in the Quran perspective. The author uses Q.S. Al-Kahf verses 65 to 70 as a material to explore and extract due to its excellent educational encounter value in it. This thesis aims to find; Teachers' rights and obligations, pupil’s rights and obligations, both characters and their relationship behavior in the verses of Moses and Khidir action as mentioned in verses 65-70. This research is based on library research (Library Research) with primary data sources contains books of classical commentary and contemporary interpretation, while secondary data consists of educational books that discuss teacher-student relationships. Furthermore collected data is analyzed by using tahlili commentary method. The author finds that: the teacher-student relationship in the verses is a relationship based on close friendship relations with maintained ethical values and mutual understanding. Similarly, students are expected to understand the rights of teachers and should uphold the rights of teachers. The relationship model is essential to be well implemented in today's education system. Given the decline of student's ethics and also the presence of teachers who are less aware of their responsibilities. It is clear it is time to apply the concept of teacher-student relationship as in al-kahf verses 65 to 70.